2017
DOI: 10.1038/tp.2017.182
|View full text |Cite
|
Sign up to set email alerts
|

Polyunsaturated fatty acid deficiency during neurodevelopment in mice models the prodromal state of schizophrenia through epigenetic changes in nuclear receptor genes

Abstract: The risk of schizophrenia is increased in offspring whose mothers experience malnutrition during pregnancy. Polyunsaturated fatty acids (PUFAs) are dietary components that are crucial for the structural and functional integrity of neural cells, and PUFA deficiency has been shown to be a risk factor for schizophrenia. Here, we show that gestational and early postnatal dietary deprivation of two PUFAs—arachidonic acid (AA) and docosahexaenoic acid (DHA)—elicited schizophrenia-like phenotypes in mouse offspring a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
50
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(57 citation statements)
references
References 83 publications
(91 reference statements)
6
50
0
1
Order By: Relevance
“…The significant overlap between the yellow expression and the yellow methylation modules mainly involves genes with functions in some metabolic processes, biosynthetic process and fatty acid oxidation, which demonstrated the potential relationship with nervous system development in previous studies [61, 70]. In particular, CpGs nearby genes SLC1A2, SLC1A3 and PRKCA from glutamate synapse showed hypo-methylation in SCZ which may lead to up-regulated expressions of these genes in astrocyte of SCZ, consistent with our results as shown in Table.S1 (Supplementary file 1).…”
Section: Discussionmentioning
confidence: 84%
“…The significant overlap between the yellow expression and the yellow methylation modules mainly involves genes with functions in some metabolic processes, biosynthetic process and fatty acid oxidation, which demonstrated the potential relationship with nervous system development in previous studies [61, 70]. In particular, CpGs nearby genes SLC1A2, SLC1A3 and PRKCA from glutamate synapse showed hypo-methylation in SCZ which may lead to up-regulated expressions of these genes in astrocyte of SCZ, consistent with our results as shown in Table.S1 (Supplementary file 1).…”
Section: Discussionmentioning
confidence: 84%
“…8 Moreover, studies on the ontogeny of MIA-induced deficits showed that these are evident at PND 70. 19,20 Ex vivo electrophysiological experiments were carried out before weaning (PND [12][13][14][15][16][17][18][19][20] to the aim of detect early abnormalities in dopamine neuron activity and synaptic properties.…”
Section: Prenatal Treatmentmentioning
confidence: 99%
“…Growing evidence suggests that gene expression modulated by PPARα might mitigate the inflammatory component that occurs in psychiatric diseases, such as depression and schizophrenia . Additionally, an association with the gene encoding for PPARα ( PPARA ) was found in patients with schizophrenia and the expression of these nuclear receptor genes was also downregulated in hair‐follicle cells from schizophrenia patients …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, prenatal experience and maternal Fads2 status have a pervasive, long-lasting influence on the brain development of the offspring [62]. Other results suggest that PUFA-deficiency during the early neurodevelopmental period in mice could model the prodromal state of schizophrenia through changes in the epigenetic regulation of nuclear receptor genes [63]. In conclusion, there is a growing body of evidence that omega-3 FA play an important role as well in the first as in the second evolution of man.…”
Section: Evolutionary Aspects Of Omega-3 Fatty Acidsmentioning
confidence: 99%